Perancangan Struktur Penyangga Lampu Sorot Kapasitas 2.000 Watt - Mufli, Mufli; Sisworo, Raden Rinova; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
Spotlights are a lighting tool in supporting an activity at night or activities in a room. The problem that occurs in the community in the lighting system is that there are still many places that have not been reached by electricity. The purpose of this study was to determine the design or design of a strong support frame structure for a 2,000 watt generator-powered floodlight. This research focuses on the design or design of tools which include selecting the sizes of the main parts and selecting materials that are in accordance with the conditions of use and calculating the strength of the tool. In this research, the dimensions of length (165cm), width (72cm), height (300cm) consisting of spotlights with a power of 400 watts as many as 4 pieces, lampposts made of UNP 75x40 iron, as well as generators as a source of electrical energy and wheels to move spotlights. in this design it is known that the critical load on the top is 152.61 kg, the critical load on the bottom is 85.44 kg, and the welding shear stress in this design is 40037. 33 N/m2. 33 N/m2. Keywords: generator, floodlight, lighting, support, design